Spatiotemporal Variations of Soil Reactive Nitrogen Oxide Fluxes across the Anthropogenic Landscape - Purchase, Megan L.; Bending, Gary D.; Mushinski, Ryan M. (Environmental science & technology, 2023)
Volatile reactive nitrogen oxides (NO y ) are significant atmospheric pollutants, including NO x (nitric oxide [NO] + nitrogen dioxide [NO2]) and NO z (nitrous acid [HONO] + nitric acid [HNO3] + nitrogen trioxide [NO3] + ...). NO y species are products of nitrogen (N) cycle processes, particularly nitrification and denitrification. Biogenic sources, including soil, account for over 50% of natural NO y emissions to the atmosphere, yet emissions from soils are generally not included in atmospheric models as a result of a lack of mechanistic data. This work is a unique investigation of NO y fluxes on a landscape scale, taking a comprehensive set of land-use types, human influence, and seasonality into account to determine large-scale heterogeneity to provide a basis for future modeling and hypothesis generation. By coupling 16S rRNA amplicon sequencing and quantitative polymerase chain reaction, we have linked significant differences in functional potential and activity of nitrifying and denitrifying soil microbes to NO y emissions from soils. Further, we have identified soils subject to increased N deposition that are less microbially active despite increased available N, potentially as a result of poor soil health from anthropogenic pollution. Structural equation modeling suggests human influence on soils to be a more significant effector of soil NO y emissions than land-use type.